Q. Solve the system of equations by elimination.−2x−3y+3z=−193x+y+2z=−162x−y+2z=−10
Add Equations to Eliminate y: First, let's add the second and third equations to eliminate y.(3x+y+2z)+(2x−y+2z)=−16+(−10)5x+4z=−26
Multiply Equations to Eliminate y: Now, let's multiply the first equation by 3 and the second equation by 2 so we can eliminate y again.(−2x−3y+3z)×3=−19×3(3x+y+2z)×2=−16×2−6x−9y+9z=−576x+2y+4z=−32
Add Equations to Eliminate y: Next, we add the new equations from the previous step to eliminate y.(−6x−9y+9z)+(6x+2y+4z)=−57+(−32)−7y+13z=−89
Align Coefficients of z: Now we have two equations:5x+4z=−26−7y+13z=−89We need to find one more equation to eliminate another variable.
Add Equations to Eliminate z: Let's multiply the first original equation by 2 and the third original equation by 3 to align the coefficients of z.(−2x−3y+3z)×2=−19×2(2x−y+2z)×3=−10×3−4x−6y+6z=−386x−3y+6z=−30
Solve for x: Now, we add these two new equations to eliminate z.(−4x−6y+6z)+(6x−3y+6z)=−38+(−30)2x−9y=−68
Substitute x into Equation: We now have three equations with two variables each: 5x+4z=−26−7y+13z=−892x−9y=−68 We can solve one of these equations for a variable and substitute it into another equation.
Multiply to Remove Fraction: Let's solve the third equation for x.2x−9y=−682x=9y−68x=29y−68
Add Equations to Eliminate y: Substitute x into the first equation we found, 5x+4z=−26.5(29y−68)+4z=−26245y−340+4z=−26
Add Equations to Eliminate y: Substitute x into the first equation we found, 5x+4z=−26. 5(29y−68)+4z=−26 245y−340+4z=−26Multiply everything by 2 to get rid of the fraction. 45y−340+8z=−52
Add Equations to Eliminate y: Substitute x into the first equation we found, 5x+4z=−26. 5(29y−68)+4z=−26 245y−340+4z=−26Multiply everything by 2 to get rid of the fraction. 45y−340+8z=−52Now, let's add this equation to the second equation we found, −7y+13z=−89, to eliminate y. (45y−340+8z)+(−7y+13z)=−52+(−89) x0
More problems from Solve a system of equations in three variables using elimination